Diversification, Dutch Disease, and Economic Growth: Options for Uganda - Thorvaldur Gylfason; Jean-Pascal Nguessa Nganou (Center for Economic Studies and ifo Institute (CESifo), 2014)
Natural resource discoveries, even when fairly modest in terms of the revenues they are expected to generate, can have significant macroeconomic effects and implications for the conduct of fiscal and monetary policy. In this respect, Uganda is no different from other oil-rich countries. In five main ways, all of which suggest the need for economic diversification as an efficient risk management strategy, the Dutch disease manifests itself through (i) An appreciation of the local currency in real terms, undermining the profitability of other export industries, and of local industries competing with imports by encouraging imports. (ii) The increased volatility of the real exchange rate induced by oscillating oil prices in world markets, which reduces investment and economic growth over time. (iii) Wage increases in the resource-intensive sector that spill over to the non-resource-based sector, further hampering employment and investment in the non-resource-based sector. (iv) Socially counterproductive rent seeking (and even plundering) in the absence of effective legal and institutional mechanisms that would ensure resource rents accrue to the rightful owners with minimal leakages, and are managed for the benefit of all. (v) Crowding out, by which natural capital (if not well managed) tends to undermine other types of capital essential to economic development, including human and social capital.
Keywords: F43; O13; O43; 330; Dutch disease; export diversification; economic growth; Uganda